Intangible Assets – Influence on the “Return On Equity” (S&P100 Index) - Nunes, Alcina (2020)
In the 21st century, the most valuable strategic resources for business enterprises will no longer be physical assets such as land and machines, but rather intangible assets (IA) such as knowledge, patents, and intellectual property rights. This study aims to analyze the effect of IA (exclusively those that are recognized and shown in the balance sheet) on the return on equity (ROE). In order to analyze the influence of IA on ROE, the study used components of the Standard and Poor 100 Index (S&P100). Due to some research restrictions, 68 companies were selected as the study’s sample. The research results were obtained using the Ordinary Least Square (OLS) method. According to our findings, the influence of IA on ROE is approximately 34% excluding goodwill and 31% including goodwill.